Calcium effect on the Nernst coefficient in double-substituted Y1-xCaxBa2Cu2.8Zn0.2Oy - Чжан Суньпэн; Виталий Эдуардович Гасумянц (Physics of Complex Systems, 2025)
We present experimental results on the temperature dependence of the Nernst coefficient in the normal state of the system Y1-xCaxBa2Cu2.8Zn0.2Oy, analyzed quantitatively using a narrow-band model jointly with temperature dependences of the thermopower. From this analysis, we determine the charge carrier mobility across all studied samples and then analyze its variation with increasing calcium content. It is shown that all experimental and calculated results can be explained if we take into account that both calcium and zinc directly affect the structure of the band responsible for the conduction process in the YBa2Cu3Oy system. Calcium introduced into the lattice compensates for local disturbances in the electronic structure created by zinc, as a result of which the values of all parameters of the normal state at x ≥ 0.125 become close to the ones characteristic of undoped YBa2Cu3Oy.